Transparency, Accountability, and the Public Role of Higher Education - Paul Standish (Educational Futures)
This paper examines the pressures imposed by a certain culture of accountability on the ways of thinking that constitute the university. It does so by, first, acknowledging but gaining some distance on complaints against performativity and, second, by examining in finer detail the notion of the performative, recalling Bourdieu’s helpful phrase: “the performative magic of institutions”. In the light of this it seeks to expose the nature of the responsibility that attaches to teaching and research in higher education, especially as these are brought together in the role of the professor. On the strength of this it identifies two “drives” that can characterise the university as a heuristic to providing a richer account of what the university might be about.